Profil Penalaran Matematis Siswa Kelas XI SMAN 6 Madiun dalam Menyelesaikan Masalah Fungsi Ditinjau dari Adversity Quotient - Mega Yulianita; Edy Suprapto; Eka Sari (Departement of Mathematics Education, 2024)
Mathematics is closely related to every dimension of life. Mathematics requires reasoning in examining abstract structures and understanding the relationship patterns within them. Reasoning is influenced and honed through individual resilience in facing difficulties to obtain a solution or what is called the adversity quotient. This research aims to describe the mathematical reasoning profile of class XI SMAN 6 Madiun tahun pelajaran 2023-2024 topic fungsi akar in terms of adversity quotient. So this type of research is descriptive qualitative with research subjects of 3 students representing each AQ group, namely climber, camper and quiter. The instruments for this research are questionnaires, mathematical reasoning tests, and interview guides. The research results showed that the climber subjects were able to fulfill all indicators of mathematical reasoning, namely making conjectures, presenting mathematical statements through writing/orally, carrying out mathematical manipulations and drawing conclusions/generalizing. The camper subject only met 2 indicators, namely proposing conjectures and presenting mathematical statements in writing/orally, the subject carried out mathematical manipulations but could not operate them correctly and did not write down conclusions from the solutions obtained. Quiiter subjects only fulfill 2 indicators, namely proposing conjectures and presenting mathematical statements through writing/orally, subjects are unable to find relevant material concepts in finding solutions to complex problems and only write conclusions from solutions to simple problems.